2013
DOI: 10.1080/01457632.2013.825154
|View full text |Cite
|
Sign up to set email alerts
|

Moving Bed Heat Exchangers for Use With Heat Storage in Concentrating Solar Plants: A Multiphase Model

Abstract: Heat storage based on particulate materials is a promising option to provide a demand-oriented electricity production with utility-scale solar power plants. For energy storage discharge, a moving bed heat exchanger is considered and its design is investigated. As a basis for a flexible design tool, a multiphase model based on the Eulerian continuum approach was set up to describe the bulk flow and the thermal performance. The model was applied to an example heat exchanger layout, and the simulation results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Recent work has identified moving packed-bed particle heat exchangers as low-cost alternatives to fluidized beds because moving packed-beds avoid the high-cost components in fluidized beds, which include pumps to fluidize the particles and recuperators to prevent large thermal loss from the fluidization gas. Baumann et al [12] developed a CFD multiphase model approach to describe the flow distribution and the thermal performance of a moving bed heat exchanger. They compared the numerically estimated heat transfer coefficient with the empirical penetration model, and concluded that the multiphase approach is well suited to predict the thermal behavior.…”
Section: Prior Workmentioning
confidence: 99%
“…Recent work has identified moving packed-bed particle heat exchangers as low-cost alternatives to fluidized beds because moving packed-beds avoid the high-cost components in fluidized beds, which include pumps to fluidize the particles and recuperators to prevent large thermal loss from the fluidization gas. Baumann et al [12] developed a CFD multiphase model approach to describe the flow distribution and the thermal performance of a moving bed heat exchanger. They compared the numerically estimated heat transfer coefficient with the empirical penetration model, and concluded that the multiphase approach is well suited to predict the thermal behavior.…”
Section: Prior Workmentioning
confidence: 99%
“…The model has also been compared to Eulerian two phase computational fluid dynamics (CFD) simulations of granular flow between pipes, in Ansys Fluent®, by Baumann and Zünft. This work was related to heat exchangers for concentrating solar power plants (Baumann & Zunft 2012;Baumann et al 2013;Baumann et al 2014). Baumann and Zünft also compared the Niegsch et al model and their CFD simulations to experimental results, collected by means of particle image velocimetry, with good agreement.…”
Section: Q = C H T Hi -T Ho = C H ε H T Hi -T P = C C T Co -T Ci = C mentioning
confidence: 99%
“…The flow rates of gas and solids were then set to the desired values, the heat input into the system was fixed, and the system was allowed to stabilize over a period of about 30 minutes, during which flow rate, temperatures, and pressures were monitored and recorded. [21,22] The downcomer of a CFB is used to supply the endothermic heat of pyrolysis of biomass (450-550 ∘ C), through wall-to-sand preheating Brems et al, 2013 [14] The downcomer of a CFB pyrolysis reaction of solid (wall-to-bed) plastic waste can be used to supply the endothermic heat of pyrolysis by heating the sand carrier to appropriate temperatures Baumann et al, 2012 and 2014 [26,27] The effect of powder properties on their use as heat transfer media in a moving bed heat exchanger (with embedded tubes) was investigated in view of concentrated solar power applications Baird et al, 2008 [28] Empirical and model fittings of experimental data from the wall to a moving bed of nickel pellets were investigated Zhang et al, 1999 [29] Characterization of local and overall gas-solid flow structure by measuring the distribution of local solids holdups and pressure gradients along the downcomer Zhang and Zhu, 2000 [30] Local solids fluxes were also calculated from the local particle velocities and solids holdups Ball and Zhu, 2001 [31] The effect of gas velocity, solids circulation rate, and axial and radial positions on the local solids flux in a gas-solids downcomer of a fluidized bed Chen and Li, 2004 [32] Probability density distribution was studied through low and high density downcomer operations and confirmed that solids flux is affecting the solids holdup Lehner and Wirth, 1999 [33] Experimental investigations concerning the local and cross-sectional solids distribution were conducted under different operating conditions and with different solids Kim et al, 2001 [34] The effects of operative conditions of subbituminous coal gasification in a downcomer reactor were experimentally determined Ma and Zhu, 1999 [35] Local heat transfer was investigated in a gas-solid concurrent downflow downcomer of a fluidized bed with FCC particles. HTC is closely related to the hydrodynamics, with bed suspension density being the most influential factor Tamarin and Gorbachev, 1968 [36] Heat transfer coefficient between a bed of moving slag particles and a vertical surface was experimentally determined in several gas atmospheres Kim et al, 1999 [37] Bed-to-wall heat transfer coefficient was determined in a downcomer reactor and results showed suspension density, gas convection, and particle size as influential factors.…”
Section: Experimental Setup and Procedure: Wall-to-bed Heat Transfermentioning
confidence: 99%